Is There a Duty to Read the News? - Berg, Amy (Journal of moral philosophy, 2023)
It seems as though we have a duty to read the news – that we’re doing something wrong when we refuse to pay attention to what’s going on in the world. But why? I argue that some plausible justifications for a duty to read the news fail to fully explain this duty: it cannot be justified only by reference to its consequences, or as a duty of democratic citizenship, or as a self-regarding duty. It can, however, be justified on the grounds that we have a positive, imperfect duty of respect for strangers, even when our actions don’t affect them directly. Reading the news is a key way, sometimes the only way, that we can respect those who are strangers to us. I close by considering some of the implications and limitations of this duty.